(x + 2)(x + 3) + (x - 3)(x - 2) - 2x (x + 1) = 0
Answers
Answered by
1
Answer:
x=6
Step-by-step explanation:
(x+2)(x+3)+(x−3)(x−2)−2x(x+1)=0
⇒x
2
+2x+3x+6+x
2
−3x−2x+6−2x
2
−2x=0
⇒2x
2
−2x
2
+5x−5x−2x+12=0
⇒−2x+12=0
⇒−2x=−12
⇒x=6
Answered by
5
EXPLANATION.
⇒ (x + 2)(x + 3) + (x - 3)(x - 2) - 2x(x + 1) = 0.
As we know that,
Evaluate the equation into simple form, we get.
⇒ (x² + 3x + 2x + 6) + (x² - 2x - 3x + 6) - (2x² + 2x) = 0.
⇒ (x² + 5x + 6) + (x² - 5x + 6) - (2x² + 2x) = 0.
⇒ x² + 5x + 6 + x² - 5x + 6 - 2x² - 2x = 0.
⇒ 2x² - 2x² + 5x - 5x - 2x + 6 + 6 = 0.
⇒ - 2x + 12 = 0.
⇒ 2x = 12.
⇒ x = 6.
Similar questions
English,
2 months ago
History,
2 months ago
World Languages,
4 months ago
Political Science,
11 months ago